On the issue of the origin of Skifo-Siberian "Animal style" - Mannay-ool, Mongush H. (The New Research of Tuva, 2009)
Tribes of the Sajano-Altay region have brought an essential contribution to creation of the Skifo-Siberian art. During the Scythian times Tuva represented one of the important centers of nomadic civilisation of Euroasian steppes. By the level of social, economic and cultural development it did not concede to other territories of the Scythian world.